The Central Role of IFI204 in IFN-β Release and Autophagy Activation during Mycobacterium bovis Infection - Chunfa, Liu; Xin, Sun; Qiang, Li; Sreevatsan, Srinand; Yang, Lifeng; Zhao, Deming; Zhou, Xiangmei (Frontiers in Cellular and Infection Microbiology, 2017)
Mycobacterium bovis (M. bovis) is the pathogen of animals and humans that can replicate in the phagosomes of myeloid cells. Cytosolic detection of bacterial products plays a crucial role in initiating the innate immune response, including autophagy activation and interferon-β (IFN-β) release. Although IFN-β release and autophagy activation have been reported during mycobacterium infection, the mechanisms underlying remains poorly defined. Here, we demonstrated that IFN-β release increases in macrophages exposed to M. bovis and this requires the activation of the DNA sensor of interferon-γ inducible protein 204 (IFI204)). Knockdown of the IFI204 in immortalized and primary murine macrophages blocked IFN-β production and autophagy marker LC3 expression. Thus, our results indicate that the IFI204 is an important sensor for innate immune responses of M. bovis infection.